Protection for the Grand Korpri Community, Victims of the Corruption Case the Director of PT Tiga Putra Mandiri - Adiswanda, Jeri Putra; Herlita Eryke (Melayunesia Law, 2025)
This study aims to analyze the form of legal protection for the Grand Korpri community in Bengkulu City who are victims of a corruption case committed by the Director of PT. Tiga Putra Mandiri Bengkulu, as well as to examine the legal responsibility of related agencies, especially the National Land Agency (BPN) of Bengkulu City. This study uses a normative juridical approach with secondary data in the form of court decisions and laws and regulations. The results of the study indicate that the actions of the Director of PT. Tiga Putra Mandiri who used land owned by the Bengkulu City Government for housing development without a permit is a form of legal violation that fulfills the elements of a criminal act of corruption as regulated in Article 2 paragraph (1) of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. In addition, the Grand Korpri community who have purchased houses on credit are the parties most disadvantaged due to the weak supervision of land administration by the BPN. The legal protection steps taken are by carrying out administrative reconciliation steps between the Bengkulu District Attorney's Office, the Bengkulu City Government, PT. Tiga Putra Mandiri, Bank Tabungan Negara (BTN) Bengkulu Branch, Bank Negara Indonesia (BNI) Bengkulu Branch and the Grand Korpri Community through the legislative mechanism of use rights or proportional compensation.